Manajemen Pendidikan Khusus di Sekolah Luar Biasa Untuk Anak Autis - Daroni, Gangsar Ali; Solihat, Gina; Salim, Abdul (Universitas Kristen Satya Wacana, 2018)
This study aims to determine the implementation of special education management at Special School for Autism. This research is descriptive qualitative research. The speakers in this research are the principal and two teachers at Special School for Autism in Karanganyar. Data were collected by interview, observation, and documentation. Data analysis techniques using Miles and Huberman models. There are three steps in this model, namely data reduction, data display, and conclusion. The implementation of special education management at Special School for Autism in coordination by a principal. In planning educational programs, tailored to the ability of each autistic student using IEP (Individual Educational Program). The school has an organizational structure that works in accordance with its duties. The principal is in charge of coordinating school management, while the teacher is responsible for the management of the class. Special School for Autism is a recently established school. The condition of autistic students who have different characteristics, the location of the foundation's office with the school is very far away, and the entry of students with different disorder conditions with autistic students makes the implementation of education management in Special School for Autism not running optimally. Therefore, schools have made efforts to minimize these barriers.